Bacterial resistance against heavy metals in Pseudomonas aeruginosa RW9 involving hexavalent chromium removal - Mat Arisah, Fatini; Amir, Amirah Farhana; Ramli, Norhayati; Ariffin, Hidayah; Maeda, Toshinari; Hassan, Mohd Ali; Mohd Yusoff, Mohd Zulkhairi (Multidisciplinary Digital Publishing Institute, 2021)
Pseudomonas aeruginosa RW9 is a promising candidate for the bioremediation of chromium hexavalent (Cr(VI)) pollution, as it resists a high concentration of up to 60 mg/L of Cr(VI). Leaving cells exposed to Cr(VI) has large bioreduction potential, implying its capacity to extract the ions from the contaminated medium. In this study, the tolerance for and distribution of Cr(VI) were investigated to identify the cells’ adaptation and removal strategies. Micro-characterization analysis was conducted to assess the effect of Cr(VI) on the cells. The cells’ elongation was observed at higher Cr(VI) concentrations, signifying their adaptation to DNA damage caused by Cr(VI) toxicity. Cr(VI) distribution analysis showed that the strain developed a complex mechanism to adapt to Cr(VI), based on surface-bound (0.46 mg/L), intracellularly accumulated (1.24 mg/L) and extracellular sequestration (6.74 mg/L), which accounted for 85% of the removal efficiency. The extracellular sequestration might be attributable to the production of metabolites, in accordance with the fourier-transform infrared spectroscopy (FTIR) spectra and orcinol analysis that confirmed the presence of a glycolipid biosurfactant, rhamnolipid. Remarkably, the rhamnolipid was slightly induced in the presence of Cr(VI). From the data obtained, it was confirmed that this local strain is well equipped to survive high doses of Cr(VI) and has great potential for application in Cr(VI) bioremediation.